Otolith Morphometrics of Selar Crumenophthalmus From Kema Strait - Taliawo, Rofino; Manginsela, Fransine B; Bataragoa, Nego E. (Jurnal Ilmiah PLATAX, 2018)
Otolith or ear stone of fish,  known as a result of biomineralization which takes place in the body of the fish. In some studies, otolith used to estimate age and stock structure of the fish.  The otolith  was categorized into three  types called sagitta, lagena and utrikulus and  the most widely studied. This study was designed to describe the characteristics  of the otolith of S. crumenophthalmus  by implementing  six index form descriptors.Tthe  study also dimed at determinition the relationship of fish length and otolith length as well as otolith width .  Linear regression approch was used to analyse the relationship of fish length and whole characteristics otolith . Those parameters were analysed using Excel and application R program  ( the package the FSA ). The results  show that otolith S.crumenophthalmus  sagitta has 6 descriptor indicees thatt are as follow: 1) the irregular surface (from factor < 1), 2) comparison against a full round (roundness ≠ 1), no 3) (full circle-shaped circularity: 21), 4) do not form a perfect square (R ≠ 1) and 5 axis) changes of 28-29 and 6) form a somewhat elongated (aspect ratio > 1). The value index  otolith form is showed ellipse.Based on the results of the analysis, the otolith left and right (length, width, perimeter, and area) otolith males S. crumenophthalmus has no different. Same alsois found on the case of males otolith, left and on right (long) females otolith S. crumenophthalmus does not differ except the width of the otolith, the area and perimeter size of a different otolith real. The relationship between  the length size and width dimensions of otolith with the total length of the fish has a linear relationship. The second parameter of the linear relationship is marked by the determination coefficient values on otolith length varies between 0,56-0,62 and its width ranged from 0.49 to 0.69. For female fish, otolith lenght detemination coefficient varies between 0.27 and 0.25 to its width ranges from 0.15 to 0.19.Key words: S.crumenophthalmus, otolith Morfometrik, Gulf of Kema AbstrakOtolit atau batu telinga ikan dikenal sebagai hasil dari biomineralisasi yang berlangsung dalam  tubuh  ikan. Pada beberapa studi, otolit digunakan  untuk mengestimasi umur ikan serta struktur stok. Dari tiga (3) organ otolit (sagitta, utrikulus dan lagena), yang paling banyak diteliti adalah otolit sagitta.Penelitian yang dilakukan bertujuan untuk mendeskripsikan karakter otolit ikan Selar crumenophthalmus (yang  mengunakan   6 deskriptor indeks bentuk) dan menentukan hubungan panjang tubuh ikan dengan panjang otolit serta lebarnya.Hubungan ukuran otolit terhadap panjang total ikan dianalis mengunakan persamaan regresi linier sederhana. Alat yang digunakan untuk menganalisis bentuk serta hubungan otolit menggunakan aplikasi Excel serta program R package FSA.Dari hasil analisis, otolit sagitta ikan Selar crumenophthalmus memiliki 6 deskriptor indeks yang hasilnya adalah : 1) permukaan yang tidak teratur (from factor < 1), 2) perbandingan terhadap bulat penuh (roundness ≠1), 3) tidak berbentuk  lingkaran penuh (circularity: 21), 4) tidak membentuk persegi sempurna (R≠1) dan 5) perubahan sumbu sebesar 28-29 serta 6) bentuk agak memanjang (aspect ratio >1). Dari nilai indeks bentuk tersebut, otolit Selar crumenophthalmus menunjukan bentuk yang elips.Berdasarkan hasil analisis, otolit kiri dan kanan (panjang, lebar, , perimeter area /luas) otolit jantan Selar crumenophthalmus tidak berbeda nyata. Sama halnya dengan otolit jantan, kiri dan kanan (panjang) otolit betina Selar crumenophthalmus tidak berbeda nyata, namun lebar otolit, area serta perimeter otolit berbeda nyata.Hubungan antara dimensi ukuran panjang dan lebar otolit dengan  panjang total  ikan memiliki hubungan linier. Hubungan linear kedua parameter tersebut ditandai dengan nilai koefisien determinasi pada panjang otolit ikan jantan  bervariasi antara 0, 56- 0, 62 dan lebarnya berkisar antara 0,49 sampai 0,69. Untuk ikan betina, koefisien deteminasi panjang otolit bervariasi antara 0,25 sampai 0,27 dan lebarnya berkisar antara 0,15 sampai 0,19.Kata kunci: Selar crumenophthalmus,  Morfometrik otolit, Teluk Kema